DEVELOPMENT FINANCING: THE SOLUTION OF THE STRUCTURAL-DISTRIBUTIVE PROBLEM - O. S. Sukharev (Финансы: теория и практика)
The article examines the process of allocation of financial resources in various areas of economic development. We analysed the impact of financing on the growth of existing activities and the emergence of new sectors of the economy that have been absent so far, for example, knowledge-intensive industries.Evaluation of the results of the distribution of financial resources between the existing economic activities, old and new combinations, and the impact of this distribution on the development of the economic system.As a basis of the study we applied Neo-Schumpeterian theory of economic development, which sees development as the emergence of new combinations. The principle of “creative destruction” describes the diversion of financial resources from old to new combinations. Most of the models used to describe economic development follow the logic of this principle. However, the emergence of a new resource (or sector, kind of activity) and a combinatorial effect make a significant contribution to the distribution of finance by use. The structure of combinations affects the distribution of financial resources, but the distribution effect is also of independent importance, as it is formed by virtue of the government’s policy of financing priority areas of economic development. In the research we used the method of structural analysis and optimization problems solving.The article substantiates that there are two basic modes of development: when there is a “rational growth” aimed at obtaining the greatest income, and when there is a “limited rational growth” associated with minimizing the risks of economic activity in obtaining an acceptable, but not the greatest income. These two modes strongly influence the allocation of resources within the “old-new” combinations of structure. The study of these regimes using optimization models of imitational property reveals the peculiarities of the influence of the distribution of financial resources on the pattern of the development, which is considered as a change in the economic structure.When planning and elaborating an economic development strategy, it is necessary to take into account the problem of the distribution of financial resources between the directions, old and new combinations with the possible effect of their mutual influence. There are two principal conditions when diversification of activities does not reduce risk, but, on the contrary, can increase it due to the current structure of the sectors, and the new combination redistributes the resource so that it can either stimulate the development of old combinations, or causes collapse of these combinations. The introduction of a new combination and the institutions for financing its development will influence this or another option. The model and approach to solving the structural and distribution’s problem in the allocation of financial and other resources we proposed is a practical tool for managing the distribution of resources in the economic system, based on the state and dynamics of existing and changing markets.